Long-Term Variations of Temperature and Precipitation in the Megacity of Istanbul for the Development of Adaptation Strategies to Climate Change - Hüseyin Toros; Mohsen Abbasnia; Mustafa Sagdic; Mete Tayanç (Advances in Meteorology)
Istanbul, as one of the four anchor megacities of Europe, has shown a rise of 0.94°C in average annual temperature over the long period of 1912–2016 under impacts of anthropogenic climate change. A notable increase in temperatures has started after the 1940s, which is in parallel with the beginning of industrialization era in Istanbul. This warming is associated with an extensive population growth and accompanied the decrease in vegetation cover. Increasing in minimum series of temperature is more evident than maximum values and the rising rate of temperature values has been more pronounced during recent decades. The first significant upward trend in precipitation series has periodically started in 1920s, while there has been a stable trend from 2001 till today. The daily average of rainfall amount increased with a mean value of 58 mm during the total study period. Rising rate of daily maximum precipitation has been more evident in the last 3 decades, which is shown by the increased frequency of heavy rainfall. In this regard, both of the temperature and precipitation series had higher mean values (13.9°C and 878 mm) for the final period (1965–2016) compared to the mean values (13.6°C and 799 mm) belonging to the first period (1912–1964).